2022
DOI: 10.1177/10525629221133369
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Leadership Education: Linking Interpersonal Skills Development to Business Needs

Abstract: A disconnect has long existed between what is typically taught in management education programs and what real-world organizations seek in their leadership candidates, particularly regarding interpersonal skills. Primary complaints from the business community revolve around issues of curriculum relevance and delivery methodologies that do not facilitate the transfer of skills learned in the classroom to the workplace. A review of the literature yields very few examples of business programs that have added cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…The leadership support and organizational culture is important in the success of hospitality education (Quttainah, 2024). Aligning leadership education with business needs bridges management education and industry demands (Fulmore et al, 2022). Fostering future workforces requires continuous learning (Torresan, 2023;Ketchiwou et al, 2022), which can be valuable for enhancing learning experiences (Khalil, 2024).…”
Section: Resultsmentioning
confidence: 99%
“…The leadership support and organizational culture is important in the success of hospitality education (Quttainah, 2024). Aligning leadership education with business needs bridges management education and industry demands (Fulmore et al, 2022). Fostering future workforces requires continuous learning (Torresan, 2023;Ketchiwou et al, 2022), which can be valuable for enhancing learning experiences (Khalil, 2024).…”
Section: Resultsmentioning
confidence: 99%
“…From the labor field, it is important that future candidates have technical skills (understood as technical skills), which refer to knowledge, that is, specific skills related to the correct performance of a specific professional field (Álvarez-Santullano et al, 2018). A connection is sought between what is typically taught in management education programs and the interpersonal skills that real-world organizations look for in their leadership candidates (Fulmore et al, 2022). Likewise, the institutions responsible for improving education recognize that Colombia has the need for higher education training that is relevant to society, so they have formulated a series of generic and specialized skills, which constitute the horizon of desirable training actions in higher education being a reference to monitor the quality of training in undergraduate academic programs.…”
Section: Conclusion Introductionmentioning
confidence: 99%
“…As a concept and as brick-and-mortar locales, higher education is under scrutiny and has been criticized for the lack of attention focused on graduates' transition from the college classroom to the workplace. Fulmore et al (2022) American management education in which they found that members of the business community wanted business schools to design education programs that were more practical…" (as cited by Fulmore et al, 2022, p. 2).…”
Section: Career Preparednessmentioning
confidence: 99%